SUPERVISI AKADEMIK TERHADAP GURU BIMBINGAN DAN KONSELING - Suparno Suparno Suparno (UNIVERSITAS BENGKULU, 2016)
The purpose of this research is to discribe the aspects of service in guidance and counseling covering the aspects of planning, qualitics, evaluation and follow up in MTs Negeri Ketahun North Bengkulu Regency. The method used in this research was descriptive to described the data more completly. Through the change on preparation guidance and counseling by usingqualitative approach. The result show that; 1) the plann academic supervision was done by MTs Negeri Ketahun North Bengkulu; 2) the action of academic supervision was done by MTs Negeri Ketahun North Bengkulu; 3) the evaluation of academic supervision was done by MTs Negeri Ketahun North Bengkulu; and 4) the follow up of academic supervision was done by MTs Negeri Ketahun North Bengkulu.Keywords: supervision, academic, guidance and counseling